Myeloperoxidase Levels Predict Executive Function - Haslacher, H.; Perkmann, T.; Lukas, I.; Barth, A.; Ponocny-Seliger, E.; Michlmayr, M.; Scheichenberger, V.; Wagner, O.; Winker, R. (International Journal of Sports Medicine, 2012)
The main purpose of the study was to investigate whether baseline myeloperoxidase (MPO) levels are associated with executive cognitive function in individuals with high physical activity. Baseline serum MPO levels of 56 elderly marathon runners and 58 controls were assessed by ELISA. Standardized tests were applied to survey domain-specific cognitive functions. Changes in brain morphology were visualized by magnetic resonance imaging (MRI). High baseline serum MPO levels correlated with worse outcome in tests assessing executive cognitive function in athletes but not in the control group (NAI maze test p<0.05, Trail Making Test ratio p<0.01). In control participants, subcortical white matter hyperintensities were associated with higher scores on the Geriatric Depression Scale (p<0.05), whereas athletes seem to be protected from this effect. During strenuous exercising, MPO as well as its educts may be elevated due to increased oxygen intake and excretion of pro-inflammatory mediators inducing host tissue damage via oxidative stress. This outweighs the potential benefits of physical activity on cognitive function.
Keywords: marathon; exercising; inflammation